Design of Arabic Language Teaching Materials to Improve Speaking ‎Skills of Nursing Study Program Students - Muna, Ani Fauzia Ainul; Alam, Fajar Nur Syah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Speaking skills are the most basic and important aspect of learning Arabic. Seeing the importance of this skill, the Nursing Study Program at Madani College of Health Sciences conducts Arabic speaking skills learning in each semester with the aim that graduates of this study program are able to communicate in their profession using Arabic, especially in Middle Eastern countries. However, the Arabic teaching materials that have been used have not been relevant to the needs of students and have not been maximized to improve students' speaking skills. The purpose of this study was to determine the design of textbooks with interactive topics adapted to the language of students, adding appropriate vocabulary and images to each material. This study used Borg and Gall's research and development (R&D) method. The sample in this study consisted of 32 1st semester students from the nursing study program. The data collection techniques used included tests, interviews, questionnaires, and documentation. The results of this study indicate that the Arabic textbook product was tested and received an assessment and validation by experts in their fields, scoring 89% with good criteria, 95% teacher assessment, and 82% student assessment. The results of student test scores after using this course book (8.2) were higher than the test scores before using the course book (5.9), leading to the conclusion that this course book design is practical, feasible, and suitable for improving the learning process.